1998
DOI: 10.1080/02841859809172223
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution MR imaging of the cutis and subcutis

Abstract: High-resolution MR imaging may narrow down the differential diagnosis of various skin diseases and may help to reduce the number of skin biopsies on certain indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Previous examinations of the skin and subcutis in BCRL have used either ultrasound (18,19) or computed tomography (CT) (20,21), while magnetic resonance imaging (MRI) has been limited to lymphedema of the leg (22,23). With regard to resolution, ultrasound (resolution 80 µm at 20 MHz) is comparable, if not better, than both CT (resolution 100–300 µm) (24) and MRI (resolution 156 µm) (25). A benefit of the current study is the use of two ultrasound machines with different frequencies, optimized for skin (20 MHz) and subcutis (7 MHz) thickness measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous examinations of the skin and subcutis in BCRL have used either ultrasound (18,19) or computed tomography (CT) (20,21), while magnetic resonance imaging (MRI) has been limited to lymphedema of the leg (22,23). With regard to resolution, ultrasound (resolution 80 µm at 20 MHz) is comparable, if not better, than both CT (resolution 100–300 µm) (24) and MRI (resolution 156 µm) (25). A benefit of the current study is the use of two ultrasound machines with different frequencies, optimized for skin (20 MHz) and subcutis (7 MHz) thickness measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that MRI with microscopy coils can serve as a diagnostic tool for various skin lesions. Krug et al (18) demonstrated that high resolution MR images obtained by a 1.0T system using a microscopy coil with an inner diameter of 75 mm enabled visualization of the dermis, subcutaneous tissue, and muscle fascia allowing for a pattern analysis that may minimize the differential diagnosis of various skin diseases and may help to reduce the number of skin biopsies in certain indications. In a study by Gufler et al (19), high-resolution MRI with a microscopy surface coil and a high-field 1.5-T MR system proved to be a suitable method to determine the extension and depth of infiltration in regards to basal cell carcinomas of the facial region.…”
Section: Discussionmentioning
confidence: 99%
“…The present results are the basis for analysis of hindfoot pathology (hindfoot trauma and chronic hindfoot disorders)(see Tables 1 and 2). Sectional planes and scanning parameters were standardized for a better comparison of imaging results [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The parameters for the gradient echo sequence (90 ms/21 ms/15°TR/TE/flip‐angle) were: section thickness 2 mm and field of view 150 mm. The scanning time was 7:18 min [12].…”
Section: Methodsmentioning
confidence: 99%